METHODS OF TEACHING THE DISCIPLINE «INFORMATION AND COMMUNICATION TECHNOLOGIES» IN PEDAGOGICAL EDUCATION - Yersultanova, Z.S.; Tsyganova, A.D.; Aytbenova, A.A. (publisher of Kostanay state pedagogical university, 2020)
The article discusses innovative methods used in teaching the discipline «Information and communication technologies» at a pedagogical university: game methods, project method, case study method, interactive methods. The conditions of successful application of the considered methods, examples of their application are analyzed.
Keywords: pedagogical methods; innovative methods; game technologies; case study; design method